Virgil Ierunca – Jurnalistul scriitor: Virgil Ierunca – a journalist and a writer - Zăbavă, Elena-Camelia (Swedish Journal of Romanian Studies, 2021)
In the second volume entitled „Necunoscutul scriitor Virgil Ierunca” (The Unknown writer Virgil Ierunca) from a series dedicated to the Romanian literature in exile (published by Aius Publishing House from Craiova), the two authors – Mihaela Albu & Dan Anghelescu – demonstrate that Ierunca was not only a good journalist and editor, but also a poet, a literary critic, a memoirist, a portraitist, and a poet. In other words – Virgil Ierunca was an authentic Romanian writer.